Identifying Appropriate Teaching and Learning Strategies for Taiwanese College Students through an Analysis of Their Internet Use Habits - Chiu, Ya-Fang (INTI University College, 2009)
This research attempts to understand the differences among junior Taiwanese college students with regard to their Internet use habits and the influence of these on their teaming involvement and preference through questionnaire survey (academic year 20052006) in the Taiwan Higher Education Database”. Survey was analyzed by means of t-test, one-way ANOVA and other statistics methods. Insights into suitable teaching and learning strategies will be correspondingly provided by discussing the differences according to gender and school types. Based on the preliminary analysis, although male and female college students were shown to have no significant statistical difference In terms of total hours of Internet use, they show significant statistical difference in four types of Internet activity. In addition, college students from different types of schools were also found to have different habits ¡n Internet use. Although the preliminary analysis indicates that college students with different hours of Internet use have no significant statistical difference in terms of satisfaction with learning achievements, the Internet use purposes demonstrate the learning preference.